Competency-Based HR Planning in Increasing Productivity of PT Ace Hardware Cimanggis Branch - Surya; Iis Sugiarti; Irmawaty; Hadi Supratikta (Indonesian Development of Economics and Administration Journal, 2023)
In today’s modern era, the existence of human resources is the main factor that determines the success or failure of an organization and company, both business and social organizations. Competency-based HR planning is an approach in human resource management (HRM) that focuses on developing and utilizing employee competencies in the organization. The type of research in this study is qualitative with descriptive methods. This study intends to provide an in-depth picture related to the object of research, namely competency-based HR planning at PT Ace Hardware Indonesia Cimanggis Branch. The data collection techniques used by researchers are observation, interviews, documentation and literature studies. The conclusion of competency-based HR planning in increasing productivity at PT Ace Hardware Indonesia Tbk is that this approach provides a solid and targeted framework for developing, maintaining, and optimizing human resources in an organization. Overall, competency-based HR planning is not just about placing the right people in the right positions, but also about creating an organizational culture that supports employee growth and well-being, which in turn can increase organizational productivity and competitiveness.